Implementation and Impacts of Education for Sustainable Development: Experience of Universitas Gadjah Mada - Laksana G. Perdamaian; Sentagi S. Utami; Budi Prayitno; Pri Joewo Guntoro (Universitas Diponegoro, 2021)
A green physical setting would need green behavior and culture to sustain and function properly. Education is a key component to form a sustainable mindset and lifestyle for society, especially youth. As a university with a vision to be a resilient and healthy campus, Universitas Gadjah Mada has actively involved in providing education for sustainable development. The activities have commenced since 2016 through Integrated Smart and Green Building research group and involve participants from both internal and external audiences. Internal target audiences were primarily freshman UGM students and later extended to include primary and high school students. External audiences were the government and stakeholders from the commercial sector. The program was designed to increase awareness on sustainable development and encourage everyone to take part to achieve its goals. Students were educated on the importance of sustainable lifestyle and expected to practice green behavior in their daily life. For stakeholders, a focus group discussion was organized to start a conversation for the formulation of green building regulation. There were observable immediate changes in cognitive and behavorial domain toward sustainable lifestyle. Sustainable development is a long term vision and it needs participation from everyone. Higher education as a center of knowledge should actively provide society with education to achieve sustainable development.